FRI0419 Intravenous immunoglobulins prevents experimental fibrosis in a murine model of systemic sclerosis. (12th June 2018) - Farhat, M.-M.; Speca, S.; Jendoubi, M.; Hauspie, C.; Guerrier, T.; Sobanski, V.; Sanges, S.; Hachulla, E.; Lefevre, G.; Labalette, M.; Dubucquoi, S.; Launay, D.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease characterised by an extensive multi-organs fibrosis. Immunosuppressants are effective in some extent but their incomplete efficacy is hampered by a higher infection risk. Intravenous immunoglobulins (IVIG) have a good safety profile, exhibit immunomodulatory and antifibrotic properties and hence could be a relevant treatment for SSc. Objectives: The purpose of this study was to investigate the effects of IVIG in an experimental model of SSc. Methods: SSc was induced in 6 weeks old Balb/c mice by subcutaneous injections of HOCl five days a week during six weeks (n=20), whereas control mice received subcutaneous injections of PBS (n=20). Human IVIG was administrated intravenously by single retro-orbital injection at a dose of 2 g/kg the first day of HOCl administration (n=20). A control group received an injection of 2% Maltose (n=20). Skin thickness was assessed during the protocol until the sacrifice (day 42). Skin tissues were collected in 4% PFA and processed for histological analysis. Dermal thickness was measured by performing a May-Grünwald–Giemsa staining of 4 µm skin sections; collagen deposition was assessed by performing a Picrosirius red-staining and quantified by using a colour deconvolution method. In addition, immunostaining of skin sections was performed in order to evaluate the α-smooth muscle actin (α-SMA) expression. Frozen skin tissues were analysed to also assess the mRNA expression of main inflammatory and pro-fibrotic genes (by quantitative reverse transcription polymerase chain reaction). Collagen deposition was also evaluated by measuring the content of hydroxyproline in 10 mg of frozen tissue. Results: Mice exposed to HOCl developed a diffuse cutaneous SSc with higher dermal thickness compared to the PBS group. IVIG significantly reduced dermal thickness and collagen deposition in HOCl-receiving mice. The amount of α-SMA positive cells evaluated by immunofluorescence was reduced in the HOCl treated mice receiving IVIG. mRNA expression profile of various markers of fibrosis (fibronectin, TGFβ) or inflammation (TNFα, IL-1β, IL-6) were also significantly decreased in the skin of HOCl mice treated with IVIG compared to HOCl-treated mice receiving 2% maltose. Conclusions: These results demonstrate the efficacy of IVIG in preventing experimental fibrosis in a HOCl murine model of SSc. Disclosure of Interest: None declared